2006
DOI: 10.1136/jcp.2005.035105
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac metastases

Abstract: Tumours metastatic to the heart (cardiac metastases) are among the least known and highly debated issues in oncology, and few systematic studies are devoted to this topic. Although primary cardiac tumours are extremely uncommon (various postmortem studies report rates between 0.001% and 0.28%), secondary tumours are not, and at least in theory, the heart can be metastasised by any malignant neoplasm able to spread to distant sites. In general, cardiac metastases are considered to be rare; however, when sought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
624
4
23

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 585 publications
(693 citation statements)
references
References 27 publications
(18 reference statements)
15
624
4
23
Order By: Relevance
“…Consistent with our finding of varying CMET location, Bussani et al reported that among 662 patients with autopsy‐evidenced CMETs, lesions were dispersed throughout the pericardium (69%), epicardium (34%), myocardium (32%), and endocardium (5%)—although location of cardiac chamber involvement was not defined 14. Among 110 patents with autopsy‐proved CMET, Klatt and Heitz reported that lung carcinoma, breast carcinoma, melanoma, and lymphoma were the most common tumor etiologies, similar to data from other autopsy data reports 1, 15.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our finding of varying CMET location, Bussani et al reported that among 662 patients with autopsy‐evidenced CMETs, lesions were dispersed throughout the pericardium (69%), epicardium (34%), myocardium (32%), and endocardium (5%)—although location of cardiac chamber involvement was not defined 14. Among 110 patents with autopsy‐proved CMET, Klatt and Heitz reported that lung carcinoma, breast carcinoma, melanoma, and lymphoma were the most common tumor etiologies, similar to data from other autopsy data reports 1, 15.…”
Section: Discussionsupporting
confidence: 89%
“…Although post-mortem studies would suggest that cardiac metastases occur frequently, many of these metastases remain clinically silent or unidentified due to overshadowing by symptoms of the primary malignancy [1]. However, secondary spread to the heart is important to recognize, as it occurs mainly in the context of disseminated disease and portends a poor prognosis [2], as illustrated by our case.…”
Section: Introductionmentioning
confidence: 77%
“…Based on data from postmortem studies of Bussani et al during the period from 1994 to 2003, the incidence of cardiac metastases involves 9.1% of early-stage cancers and 14.2% of metastatic. The most common sites of origin include the lung (pleural mesothelioma 48.4%, adenocarcinoma 21%, squamous-cell carcinoma 18.2%), skin (melanoma 27.8%), breast (15.5%) and undifferentiated carcinomas (19.5%) [1].…”
Section: Discussionmentioning
confidence: 99%
“…Purulent pericarditis is present in a wide variety of pathological conditions with varying etiologies such as immunosuppression and chronic diseases (e.g., alcohol abuse, rheumatoid arthritis), but is commonly secondary to injury, cardiac procedures, or insult to the pericardium [1][2][3]. There is considerable urgency to establish a correct diagnosis, because if left untreated, the combination of tamponade and sepsis results in a mortality rate approaching 100% [4][5][6].…”
Section: Introductionmentioning
confidence: 99%